Cognitive neuropsychology in clinical practice - Margolin, David Ira (Oxford University Press, 1992)
The goal of this text is to introduce cognitive neuropsychology to a broad audience of clinicians and researchers. The contributors describe how the vocabulary, theoretical framework and information-processing models of cognitive psychology are applied to disorders of higher cortical function.